Phenotypic expression of ARVC: How 12 lead ECG can predict left or right ventricle involvement. A familiar case series and a review of literature. (1st June 2017) - Gaido, Luca; Battaglia, Alberto; Matta, Mario; Giustetto, Carla; Frea, Simone; Imazio, Massimo; Richiardi, Elena; Garberoglio, Lucia; Gaita, Fiorenzo
Abstract: Aims: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited heart-muscle disease primarily affecting the right ventricle (RV) and potentially causing sudden death in young people. The natural history of the disease is firstly characterized by a concealed form progressing over a biventricular involvement. Three different cases coming from the same family are presented together with a review of the literature. Methods and results: Multi-parameter analysis including imaging and electrocardiographic analysis is presented since the first medical referral with follow-up ranging from 11 to 38 years. Case 1 presented a typical RV involvement in agreement with the ECG pattern. Case 2 presented a prevalent left ventricular involvement leading from the beginning to a pattern of dilated cardiomyopathy in agreement with his ECG evolution over the years. On the other side, Case 3 came to observation with a typical RV involvement (similar to Case 1) but with ECG evolution of typical left ventricle involvement (similar to Case 2). The genetic analysis showed a mutation in desmoglein-2 ( DSG2 ) gene: p. Arg49His. Comparison between size and localization of ventricular dyskinesia at cardiovascular imaging and the surface 12 lead electrocardiography are proposed. Conclusions: ARVC may lead to an extreme phenotypic variability in clinical manifestations even within patients coming from the same family in which ARVC is caused by the same genetic mutation. ECG progression over time reflects disease evolution and in particular cases may anticipate wall motion abnormalities by years.